"I'd like an abortion please": rethinking unplanned pregnancy narratives in contemporary American cinema. Issue 3 (3rd April 2019) - Hair, Melissa
Abstract: Released in 2014 and 2015, respectively, the American indie films Obvious Child and Grandma each feature a central protagonist who is dealing with an unplanned pregnancy and is pursuing an abortion. These pro-choice narratives not only challenge Hollywood cinema's repetitive depiction of unplanned pregnancies that result in motherhood, but they critique the dominant political and societal discourses surrounding abortion and women who choose to terminate pregnancies. Tracing the history of cinematic portrayals of unplanned pregnancy, and reflecting upon how post-feminist culture has positioned the notion of choice, this paper notes the significance of Obvious Child and Grandma as films that not only feature abortion as a central theme, but utilize comedy in their navigation of a controversial subject. Furthermore, this paper argues that in their frank and positive engagement with termination as a potential resolution to an unplanned pregnancy, these films offer important attempts to destigmatize the subject of abortion.